Sistem Aplikasi Terintegrasi Pelaporan Keadaan Darurat di Jalan tol Berbasis NodeMCU - Griffani Megiyanto Rahmatullah; Andry Haidar; Idhamartya Wulani; Aldiyans Nurcahyo; Ajeng Denita Khoerunnisa (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
An emergency on a highway is an incident that occurs suddenly and requires a fast and precise handling process. Hotline numbers on highways are still used as a reporting system but often experience busy tones and only rely on GSM mode. The purpose of this research is to make innovations to make it easier to report emergencies quickly and accurately on highways. Internet technology was chosen because the internet is an open long-distance global communication and GSM was chosen because not all locations have internet networks. The system works is that the highway users press one of the pushbuttons according to the emergency experience, then the microcontroller will activate the GPS to detect the location of the reporter and send it to the relevant agencies via the android application, SMS, or email. When the data is successfully sent, the LCD displays a notification. In testing, the results of the GPS error were 34%, while the push button was 0%, the process of sending and receiving data has a time tolerance of no more than 15 seconds. From the test, it can be concluded that the realization of the tools and applications is in accordance with the designed specifications.